The Recent Collection of Climacodon roseomaculatus (Hydnum roseomaculatum Henn. & E. Nyman) from The Type Locality (Indonesia) - Putra, Ivan Permana; Nurhayat, Oktan Dwi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Climacodon roseomaculatus is a fleshy species of Polyporales with a hydnoid hymenophore. The species’s distribution in Indonesia was reported six times from 1923 to 1961 from West Java and East Java collection to date, there have been no following updates on the collection and occurrence status of C. roseomaculatus in Indonesia. During a fungus foray in 2023, some red to pink basidiomata of Climacodon were spotted in Semarang, Central Java, Indonesia. The current study aimed to determine the taxonomical position of Climacodon BO24632 based on morphological evidence. Fresh materials were used for the investigation of macro- and micromorphological characters. The result showed that Climacodon BO24632 was identified as C. roseomaculatus based on distinctive features of stipe and gleocystidia. Climacodon roseomaculatus BO24632 is closely related to C. sanguineus with blood-red to pink basidiomata, cylindrical spines of hymenophores, and ellipsoid basidiospores. However, the former species lacks a well-developed stipe and has thin to thick-walled gloeocystidia. This study is the first report on the distribution of C. roseomaculatus from Central Java, Indonesia. In addition, the current work is the latest information and herbarium collection of C. roseomaculatus after more than fifty years of hiatus in Indonesia. We expect that the same species also occur in many different locations in Indonesia; thus need a warrant of collections.